Crisis, Work and (Un)Employment (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.6136.207-216The objective of this work is to initiate a reflection on the impact of the current crisis in the transformation process of the organization of work and industrial relations underway in the Brazilian industry. The theme of the crisis is usually approached from its more immediate effects: inflation and unemployment. But we would like to start addressing it from an earlier period: the period of economic growth known as the "Brazilian miracle" (1969-1973). And yet, treat it from the point of view of employment. We intend from the evolution of industrial employment and characteristics of technical and social division of labor and its organization within the Brazilian industry from the early '70s. The 70 in Brazil is characterized as a period of great industrial expansion and , although the symptoms of the crisis and the economic recession are being felt from 1974 , they will only manifest more clearly the level of industrial employment from 1981.